Genomic Evaluation of Assisted Gene Flow Options in an Endangered Rattlesnake - Samarth Mathur; H. Lisle Gibbs (Molecular Ecology, 2025)
Assisted gene flow is used to counteract genetic erosion in small populations of endangered species, yet an evaluation of genetic compatibility of potential donor populations and recipient populations is rare. We developed new metrics for assessing the genetic impact of genetic augmentation based on genotype identity of functional variants between donor and recipient genomes and used these metrics to evaluate options for assisted gene flow in Eastern Massasauga rattlesnake ( Sistrurus catenatus ) populations in Ohio, USA. We used putatively deleterious variants and genetic variants likely under positive selection (termed ‘adaptive’ variants) as the two components of functional variation. For potential donor and recipient populations, we estimated three key aspects of genetic compatibility: (a) introduction of novel variants, (b) masking or unmasking of existing deleterious variants and (c) potential for outbreeding depression through disruption of local adaptation. The main impact of augmentation from diverse donor populations was to introduce novel deleterious variants and to a lesser extent novel adaptive variants into each recipient population. Both donor populations had a similar minor impact in terms of masking existing deleterious variants. Finally, only ~7% of adaptive variants show evidence for local adaptation, arguing that the negative effect of outbreeding depression would be small. These results draw attention to the importance of considering the potential impact of both deleterious and adaptive genetic variants in augmentation efforts and suggest that in the case of these endangered rattlesnakes, the net effect of proposed assisted gene flow may lead to an increase in absolute levels of mutation load.

Genetic mechanisms and biological processes underlying host response to ophidiomycosis (snake fungal disease) inferred from tissue‐specific transcriptome analyses - Samarth Mathur; Ellen Haynes; Matthew C. Allender; H. Lisle Gibbs (Molecular Ecology, 2024)
Emerging infectious diseases in wildlife species caused by pathogenic fungi are of growing concern, yet crucial knowledge gaps remain for diseases with potentially large impacts. For example, there is detailed knowledge about host pathology and mechanisms underlying response for chytridiomycosis in amphibians and white‐nose syndrome in bats, but such information is lacking for other more recently described fungal infections. One such disease is ophidiomycosis, caused by the fungus Ophidiomyces ophidiicola , which has been identified in many species of snakes, yet the biological mechanisms and molecular changes occurring during infection are unknown. To gain this information, we performed a controlled experimental infection in captive Prairie rattlesnakes ( Crotalus viridis ) with O. ophidiicola at two different temperatures: 20 and 26°C. We then compared liver, kidney, and skin transcriptomes to assess tissue‐specific genetic responses to O. ophidiicola infection. Given previous histopathological studies and the fact that snakes are ectotherms, we expected highest fungal activity on skin and a significant impact of temperature on host response. Although we found fungal activity to be localized on skin, most of the differential gene expression occurred in internal tissues. Infected snakes at the lower temperature had the highest host mortality whereas two‐thirds of the infected snakes at the higher temperature survived. Our results suggest that ophidiomycosis is likely a systemic disease with long‐term effects on host response. Our analysis also identified candidate protein coding genes that are potentially involved in host response, providing genetic tools for studies of host response to ophidiomycosis in natural populations.

The long‐standing significance of genetic diversity in conservation - J. Andrew DeWoody; Avril M. Harder; Samarth Mathur; Janna R. Willoughby (Molecular Ecology, 2021)
Since allozymes were first used to assess genetic diversity in the 1960s and 1970s, biologists have attempted to characterize gene pools and conserve the diversity observed in domestic crops, livestock, zoos and (more recently) natural populations. Recently, some authors have claimed that the importance of genetic diversity in conservation biology has been greatly overstated. Here, we argue that a voluminous literature indicates otherwise. We address four main points made by detractors of genetic diversity's role in conservation by using published literature to firmly establish that genetic diversity is intimately tied to evolutionary fitness, and that the associated demographic consequences are of paramount importance to many conservation efforts. We think that responsible management in the Anthropocene should, whenever possible, include the conservation of ecosystems, communities, populations and individuals, and their underlying genetic diversity.

Episodic positive diversifying selection on key immune system genes in major avian lineages - Jennifer Antonides; Samarth Mathur; J. Andrew DeWoody (Genetica, 2019)

Evidence of genetic erosion in a peripheral population of a North American game bird: the Montezuma quail (Cyrtonyx montezumae) - Samarth Mathur; John M. Tomeček; Ashlyn Heniff; Ryan Luna; J. Andrew DeWoody (Conservation Genetics, 2019)